Product - Service System Inventory Control For Malaysian Palm Oil Agribusiness - Nina Iwani, A. Zailaini; Siti Zubaidah, Ismail (Penerbit UMP, 2019)
This research deals with the study of Product – Service System (PSS) and inventory control for Malaysian palm oil plantation company. PSS is a managing system that combining product and service in one system. PSS is essential to provide better environmental impart, improve competitiveness and to help the company satisfy the demand from customer. However, PSS could not be running smoothly when the inventory of product and service are managed in separate interface systems, which is by using manual inventory control like Microsoft Excel and handwriting documentation. In order to make PSS inventory control easier and systematic, an inventory application system is developed. This research is focusing on developing a PSS inventory control tool which could help in decision and calculation making for product and service of palm oil plantation.